The judicial application of human rights law : national, regional and international jurisprudence / Nihal Jayawickrama. - Jayawickrama, Nihal (Cambridge University Press, 2017)
Since the proclamation of the Universal Declaration of Human Rights, over 165 countries have incorporated human rights standards into their legal systems: the resulting jurisprudence from diverse cultural traditions creates new dimensions to concepts first articulated in 1948. In this revised second edition, Nihal Jayawickrama draws on extensive sources to encapsulate the judicial interpretation of human rights law in one comprehensive volume. Jayawickrama covers the case law of the superior courts of 103 countries in America, Europe, Africa, Asia, the Caribbean and the Pacific, as well as jurisprudence of human rights monitoring bodies. He analyses the judicial application of human rights law to demonstrate empirically the universality of contemporary human rights norms. This definitive volume is essential for legal practitioners, and government and non-governmental officials, as well as academics and students of both constitutional law and the international law of human rights.